Penguatan Digital Marketing Percetakan Kasandi Foil Pond Dalam Mengoptimalkan Jangkauan Pasar Dan Penjualan - Ayuningtyas Kasandi; Sulartopo; Aris Sarwo Nugroho (UNIVERSITAS STEKOM, 2026)
This study aims to analyze the strengthening of digital marketing at Kasandi Foil Pond Printing in optimizing market reach and sales. This study uses a qualitative approach with data collection techniques including observation, interviews, and documentation involving the business owner directly. The result show that the implementation of digital marketing is still not optimal, as indicated by the Instagram account that has not been actively used and the use of WhatsApp which is still limited to simple communication and has not been structured as a marketing strategy. The strengthening efforts are carried out through three main strategies, namely optimizing the use of social media, creating attractive visual content, and improving online customer interaction. The visual content created using applications such as Canva and CorelDRAW is able to increase the attractiveness of promotions and attract potential customers. In addition, consistency in posting content and quick responses through WhatsApp also contribute to increased interaction and transaction opportunities. Therefore, strengthening digital marketing based on visual media and digital interaction has the potential to increase market reach and sales if implemented consistently.